Corrigendum to: Changes in smoking, drinking, overweight and physical inactivity in young Australian women 1996–2013. (7th December 2017) - Powers, Jennifer R.; Loxton, Deborah; Anderson, Amy E.; Dobson, Annette J.; Mishra, Gita D.; Hockey, Richard; Brown, Wendy J.
Abstract : Issue addressed: Smoking, risky drinking, overweight and obesity, and physical inactivity are health‐risk factors (HRFs) that contribute significantly to morbidity worldwide. Several initiatives have been introduced over the past two decades to reduce these HRFs. This paper examines changes in the prevalence of HRFs in young women (aged 18–23 years) between 1996 and 2013, overall and within demographic groups. Methods: Data from two cohorts of the Australian Longitudinal Study on Women's Health, born in 1973–78 ( n =14247) and 1989–95 ( n =17012) were weighted to provide national estimates. Prevalence ratios were used to compare HRFs in 2013 relative to 1996. Results: In 1996, 32% were current smokers, 38% were risky drinkers, 22% were overweight or obese and 7% were physically inactive. In 2013, corresponding estimates were 19%, 35%, 33% and 6%. Between 1996 and 2013, overall smoking prevalence decreased, but remained over 43% among least educated women. Overweight and obesity increased in all demographic groups. Conclusions: The findings suggest that only smoking, which has been the subject of changes in taxation, legislation and regulation, declined significantly, in all except the least educated women. In contrast, the prevalence of overweight and obesity, which has largely been addressed through awareness campaigns and voluntary actions by the food industry, increased markedly in all demographic sub‐groups. So what?: The findings show that comprehensive health promotion interventions, such as those for tobacco control, are successful (but may still be ineffective among less educated women). In contrast the measures to control population weight gain among young women have been futile so far.